2009
DOI: 10.2135/cropsci2008.04.0192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturity on Seed Composition in the Early Soybean Production System as Measured on Near‐Isogenic Soybean Lines

Abstract: The effect of maturity (time to maturity) on seed composition in soybean [Glycine max (L.) Merr.] genotypes is not well understood because maturity is generally confounded with genotypic background. Therefore, the effects of maturity on seed composition were estimated in two sets of near isogenic soybean lines (‘Clark’ and ‘Harosoy’), where the maturity of each line within a set varied, but all had a common genotypic background. There was a positive linear relationship between protein concentration and maturit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
168
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(193 citation statements)
references
References 26 publications
21
168
2
2
Order By: Relevance
“…For example, maximum temperature was highest at 33.2˚C, 34.3˚C, and 31.3˚C in July, August, and September respectively during critical reproductive stages in Milan 2010, and only 50 and 9 mm of rainfall were recorded in August and September (seed-fill stage period) at Milan 2010 ( Table 5). It was shown that maximum temperature had significant effects on seed protein, oil, and fatty acids, and the increase or decrease of seed oil or protein concentration dependent on the temperature range under which soybean seed mature [18]. Other researchers also found that maximum temperatures correlated better with seed composition than minimum temperatures [61,62].…”
Section: Seed Yield Protein Oil and Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, maximum temperature was highest at 33.2˚C, 34.3˚C, and 31.3˚C in July, August, and September respectively during critical reproductive stages in Milan 2010, and only 50 and 9 mm of rainfall were recorded in August and September (seed-fill stage period) at Milan 2010 ( Table 5). It was shown that maximum temperature had significant effects on seed protein, oil, and fatty acids, and the increase or decrease of seed oil or protein concentration dependent on the temperature range under which soybean seed mature [18]. Other researchers also found that maximum temperatures correlated better with seed composition than minimum temperatures [61,62].…”
Section: Seed Yield Protein Oil and Fatty Acidsmentioning
confidence: 99%
“…The different concentrations of seed constituents among years in both locations reflected the effect of environmental factors on seed composition constituents. It was reported that seed constituents were affected by environment [16,17,40], temperature [17,18], drought [19,21,22,40], and nutrients in soil and seed [3][4][5]. It was reported that seed constituents vary in the same soybean cultivar grown in different years or under different environments in the same year [26].…”
Section: Seed Yield Protein Oil and Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature seeds were ground using a Laboratory Mill 3600 (Perten, Springfield, IL, USA), and the ground samples were analyzed for minerals, N, S, and C, by digesting 0.6 g of the grounddried plant materials in HNO 3 in a microwave digestion system as detailed elsewhere [29,30]. Potassium was determined by inductively coupled plasma spectrometry [29,30].…”
Section: Determination Of Seed Minerals N S and Cmentioning
confidence: 99%
“…Boron concentration was determined according to Azomethine-H method [19,[32][33][34]. Briefly, 1 g of dry sample was placed in a porcelain crucible for ashing at 500°C for 8 hr.…”
Section: Boron Determinationmentioning
confidence: 99%